Critical Review: Antioxidant Properties and Antibiotic Mechanism of Honey against Infectious Diseases - Dluya, Thagriki (International Journal of Advances in Life Science and Technology, 2015)
The advent of antibiotics in modern western medicine has made the use of honey in the treatment of infectious diseases abandoned. Hence this review exposes why honey remains the best antibiotic and its potency as an antioxidant, antibacterial, and anti-inflammatory. Honey possesses some vital components such as Methylgyloxal, Bee defensin-1, Hydrogen peroxide, osmotic effect and phenolic compounds. Honey also possesses properties that inhibit the formation of biofilms. These made honey more powerful because it prevents the formation of antibiotic-resistant bacteria while conventional antibiotic fail because they only target the essential growth processes of bacteria and this allows bacteria to build up resistance over time.